PKM2: A Potential Regulator of Rheumatoid Arthritis via Glycolytic and Non-Glycolytic Pathways - Xu, Danyi; Liang, Junyu; Lin, Jin; Yu, Chaohui (Frontiers in Immunology, 2019)
Immunometabolism has become a new perspective on the pathogenesis of rheumatoid arthritis (RA). Recent years there have been researches focusing on intracellular glucose metabolism in the pathogenesis of RA. Existing researches have revealed the up-regulation of glycolysis in RA synovial tissues, meanwhile, glycolysis inhibitors can significantly inhibit synovitis. Pyruvate kinase (PK) is a key enzyme in glycolysis, it catalyzes the final rate limiting step in glycolysis. As an isoform of PK, PKM2 provides favorable conditions for the survival of tumor cells via its glycolytic or non- glycolytic functions, which has become a potential therapeutic target in tumors. RA synovium has the characteristic of tumor-like growth, coincidentally, increased expression of PKM2 was identified in the synovial tissue of RA patients in recent researches, indicating the underlying role of PKM2 in RA. There is potential value of PKM2 as a new therapeutic target or biomarker for RA, however, its exact role in RA remains unclear. The properties of PKM2 and existing researches concerning PKM2 and RA were thoroughly reviewed and summarized, and the possible role and mechanism of PKM2 in RA were discussed in this review.